Automated mandatory bolus versus basal infusion for maintenance of epidural analgesia in labour - Sng, Ban Leong (Cochrane Database Syst Rev, 2018)
BACKGROUND: Childbirth may cause the most severe pain some women experience in their lifetime. Epidural analgesia is an effective form of pain relief during labour and is considered to be the reference standard. Traditionally epidural analgesia has been delivered as a continuous infusion via a catheter in the epidural space, with or without the ability for the patient to supplement the analgesia received by activating a programmable pump to deliver additional top‐up doses, known as patient‐controlled epidural analgesia (PCEA). There has been interest in delivering maintenance analgesic medication via bolus dosing (automated mandatory bolus ‐ AMB) instead of the traditional continuous basal infusion (BI); recent randomized controlled trials (RCTs) have shown that the AMB technique leads to improved analgesia and maternal satisfaction. OBJECTIVES: To assess the effects of automated mandatory bolus versus basal infusion for maintaining epidural analgesia in labour. SEARCH METHODS: We searched CENTRAL, MEDLINE, Embase, the World Health Organization International Clinial Trials Registry Platform (WHO‐ICTRP) and ClinicalTrials.gov on 16 January 2018. We screened the reference lists of all eligible trials and reviews. We also contacted authors of included studies in this field in order to identify unpublished research and trials still underway, and we screened the reference lists of the included articles for potentially relevant articles. SELECTION CRITERIA: We included all RCTs that compared the use of bolus dosing AMB with continuous BI for providing pain relief during epidural analgesia for labour in women. DATA COLLECTION AND ANALYSIS: We used the standard methodological procedures expected by Cochrane. Our primary outcomes were: risk of breakthrough pain with the need for anaesthetic intervention; risk of caesarean delivery; risk of instrumental delivery. Secondary outcomes included: duration of labour; local anaesthetic consumption. We used GRADE to assess the certainty of evidence for each outcome. MAIN RESULTS: We included 12 studies with a total of 1121 women. Ten studies enrolled healthy nulliparous women only and two studies enrolled healthy parous women at term as well. All studies excluded women with complicated pregnancies. There were variations in the technique of initiation of epidural analgesia. Seven studies utilized the combined spinal epidural (CSE) technique, and the other five studies only placed an epidural catheter without any intrathecal injection. Seven studies utilized ropivacaine: six with fentanyl and one with sufentanil. Two studies used levobupivacaine: one with sufentanil and one with fentanyl. Three used bupivacaine with or without fentanyl. The overall risk of bias of the studies was low. AMB probably reduces the risk of breakthrough pain compared with BI for maintaining epidural analgesia for labour (from 33% to 20%; risk ratio (RR) 0.60; 95% confidence interval (CI) 0.39 to 0.92, 10 studies, 797 women, moderate‐certainty evidence). AMB may make little or no difference to the risk of caesarean delivery compared to BI (15% and 16% respectively; RR 0.92; 95% CI 0.70 to 1.21, 11 studies, 1079 women, low‐certainty evidence). AMB may make little or no difference in the risk of instrumental delivery compared to BI (12% and 9% respectively; RR 0.75; 95% CI 0.54 to 1.06, 11 studies, 1079 women, low‐certainty evidence). There is probably little or no difference in the mean duration of labour with AMB compared to BI (mean difference (MD) −10.38 min; 95% CI −26.73 to 5.96, 11 studies, 1079 women, moderate‐certainty evidence). There is probably a reduction in the hourly consumption of local anaesthetic with AMB compared to BI for maintaining epidural analgesia during labour (MD −1.08 mg/h; 95% CI −1.78 to −0.38, 12 studies, 1121 women, moderate‐certainty evidence). Five out of seven studies reported an increase in maternal satisfaction with AMB compared to BI for maintaining epidural analgesia for labour; however, we did not pool these data due to their ordinal nature. Seven studies reported Apgar scores, though there was significant heterogeneity in reporting. None of the studies showed any significant difference between Apgar scores between groups. AUTHORS' CONCLUSIONS: There is predominantly moderate‐certainty evidence that AMB is similar to BI for maintaining epidural analgesia for labour for all measured outcomes and may have the benefit of decreasing the risk of breakthrough pain and improving maternal satisfaction while decreasing the amount of local anaesthetic needed.